2017
DOI: 10.1051/mbcb/2016056
|View full text |Cite
|
Sign up to set email alerts
|

Tooth replantation: an update

Abstract: -Introduction:Intentional replantation is a recognized endodontic procedure in cases in which root canal and surgical endodontic treatments are not recommended. Although not frequently used, intentional replantation is a treatment option that dentists should consider. Three keys point should be keep in mind to ensure the success of replantation procedure. To overcome any complications, the surgical procedure have to be rigorous, the extra-alveolar time properly managed, and the splint adapted. In the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…It has been found that the viability of PDL exposed to the extraoral environment decreased rapidly after 18 min; hence, the extraoral procedure time should be kept minimal to obtain optimal healing. [14] In the present case, the extra oral wet time was minimal and was only 10 min. During the 10 min of instrument retrieval and apicectomy followed by root-end filling, the tooth was kept immersed in normal saline in an impression.…”
Section: Discussionmentioning
confidence: 49%
“…It has been found that the viability of PDL exposed to the extraoral environment decreased rapidly after 18 min; hence, the extraoral procedure time should be kept minimal to obtain optimal healing. [14] In the present case, the extra oral wet time was minimal and was only 10 min. During the 10 min of instrument retrieval and apicectomy followed by root-end filling, the tooth was kept immersed in normal saline in an impression.…”
Section: Discussionmentioning
confidence: 49%
“…The viability of PDL exposed to the extraoral environment, decreases rapidly after 18 min, making it necessary to reduce this time for successful replantation to occur. [ 9 ] However, so far no attempts have been made, to regenerate the degenerated PDL. In this case, PRF was used in the injectable form instead of the regular membrane form since it occupies less space and possesses better properties than the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Las etapas posteriores a la extracción y previas a la reimplantación se deben realizar en un tiempo extraoral inferior a 15 minutos para asegurar la máxima vitalidad de las células del ligamento periodontal 7 . Este aspecto es crucial en el tratamiento y es el principal predictor de fracaso, con un riesgo de complicaciones (reabsorción externa y/o anquilosis) 1.7 veces más grande para los dientes reimplantados en un tiempo mayor, donde se ve comprometida la sobrevivencia de las células del LP expuestas al ambiente extraoral 13,16 .…”
Section: Principios Y Técnicaunclassified